Reproductive Performance of Beef Cattle Raised Under SPR Program in Tegal Regency - Aji Gunawan; Akhmad Sodiq; Krismiwati Muatip; Novie Andri Setianto (Buletin Peternakan, 2020)
The purpose of this research was to assess the reproductive performance of beef cattle based on different production systems. Survey research was carried out in Margasari Subdistrict, Tegal Regency, Central Java Province, in 13 farmer groups (a total of 188 breeders and 557 beef cattle) who took shelter in the SPR Program The qualitative and quantitative design framework is used to obtain comprehensive data. The questionnaire was used to get data and respondents determined by census method. SPSS software is used to analyze data. The results showed that 38.46% of farmer groups implemented a crop-livestock-system (CLS), 30.77% of farmer groups implemented a livestock-forestry system (LFS), and 30.77% of farmer groups implemented a crop-livestock-forestry-system (CLFS) in producing beef cattle. The results of the present study were significantly (P<0.05) there were differences in each reproductive performance parameter (BCS, S / C, CR, CI, and CC), which was observed in each beef production system (CLFS, CLS, and LFS). The results of this study also provide an overview of the simultaneous effects on the application of the production system to the reproductive performance of beef cattle. Although there has been certain variation between the production systems, the reproductive performance of the observed beef cattle has not been satisfactory. Improving nutrition management in cattle is needed to realize successful reproductive performance.